2001
DOI: 10.1111/j.1439-0434.2001.tb03865.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Resistance to Fusarium Wilt in Tomato Induced by Phytopthora cryptogea

Abstract: Under climate chamber conditions, suppression of tomato wilt disease caused by Fusarium oxysporum f. sp. lycopersici (FOL) was obtained by spraying a suspension of Phytophthora cryptogea (Pc) zoospores on the green parts of two tomato cultivars, Danish Export (susceptible) and Elin F1 (moderately resistant). Direct competitive or antagonistic interaction between Pc and FOL in the soil or on the root surfaces was ruled out, but not interaction within the stems of plants. After Pc application followed by FOL ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The nature and composition of ISR strongly depends on the tripartite combination plant-BCA-pathogen (Duijff et al, 1998 ; Tjamos et al, 2005 ) and the overlap between SAR and ISR could be much larger than only through the reported key marker NPR1 (Pieterse et al, 1998 ). In this manuscript, a clear distinction is made between ISR that is induced by BCAs before (ISR-prime) and after (ISR-boost) additional inoculation with a pathogen, a distinction earlier observed by others (van Wees et al, 1999 ; Attitalla et al, 2001 ; Harman et al, 2004 ; Verhagen et al, 2004 ). In 2006, a consortium of different research groups defined the concept of priming in plant defense as follows: various treatments, like inoculation with pathogens or BCAs, are said to prime plants or – in other words – prepare the plants’ defense system to respond to stresses more quickly and aggressively (Prime-A-Plant Group et al, 2006 ).…”
Section: Introductionmentioning
confidence: 74%
“…The nature and composition of ISR strongly depends on the tripartite combination plant-BCA-pathogen (Duijff et al, 1998 ; Tjamos et al, 2005 ) and the overlap between SAR and ISR could be much larger than only through the reported key marker NPR1 (Pieterse et al, 1998 ). In this manuscript, a clear distinction is made between ISR that is induced by BCAs before (ISR-prime) and after (ISR-boost) additional inoculation with a pathogen, a distinction earlier observed by others (van Wees et al, 1999 ; Attitalla et al, 2001 ; Harman et al, 2004 ; Verhagen et al, 2004 ). In 2006, a consortium of different research groups defined the concept of priming in plant defense as follows: various treatments, like inoculation with pathogens or BCAs, are said to prime plants or – in other words – prepare the plants’ defense system to respond to stresses more quickly and aggressively (Prime-A-Plant Group et al, 2006 ).…”
Section: Introductionmentioning
confidence: 74%
“…For instance, Duijff et al (1998) investigated that P. fluorescens WCS417r could induce systemic resistance to suppress of Fusarium wilt of tomato. Otherwise, some non-pathogen fungi, such as Phytophthora cryptogea , were also reported to have the ability to induce systemic resistance to Fon in the host (Attitalla et al, 2010). In our study, as shown in Figure 2, 3, we found that the transcripts of two tested genes, Cla01114 and Cla005426 , were both generally stronger in the roots of watermelon pretreated with B. velezensis F21 and then challenged with Fon from 3 dpt to 9 dpt and reached their maximums at 3 dpt compared with the control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best strategies developed to manage various diseases is induced resistance. It has been found that pre-application of tomato seedling with bio-agents, plant extracts, avirulent races of pathogens and some inorganic chemical like phosphate salt, (dipotassium/sodium or tripotassium) silicon (SiO 2 ) provided the systemic induced resistance in various crops [2][3][4][5][6][7][8][9]. Biochemical and physiological changes associated with induction of resistance are due to the response to inducing agents which are in the form like phytoalexins (Paxtron), lignin [10], callose [11] and plant pathogenesis related proteins [5].…”
Section: Introductionmentioning
confidence: 99%